(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores the growing role of artificial intelligence (AI) in modern linguistics. It analyzes how AI technologies, particularly natural language processing (NLP), are transforming the study of language, including syntax, semantics, and pragmatics. The paper also examines the benefits and challenges of integrating AI into linguistic research and language education. Special attention is given to machine translation, speech recognition, and corpus linguistics. The findings suggest that AI not only enhances linguistic analysis but also reshapes traditional approaches to language study.